SOMA: SCREENING AND SOMATIC HEALTH INTERVENTION PROGRAM FOR PEOPLE WITH SEVERE MENTAL ILLNESS - Zahrádka-Köhlerová, Michaela; Páv, Marek; Gojda, Jan; Kynštová, Hana; Wiseman, Chantelle; Tašková, Ivana; Selinger, Eliska; Hollý, Martin; Mužík, Jan (Psychiatria Danubina, 2024)
Progress in psychiatric treatment has led to important improvements in the quality of life of patients with severe mental illness (SMI). Nevertheless, the life expectancy of patients with SMI remains two decades shorter than that of the general population, and the most prevalent cause of death is cardiovascular disease. Given that the delivery of somatic care to a population of individuals with mental illness is specific, we developed a screening and intervention programme aimed at this vulnerable population. The "SOMA" programme is a complex somatic health intervention system consisting of screening and a set of interventions. Risk screening is evaluated automatically; the interventions include dietary intervention, healthy lifestyle education (HSE), physiotherapy, kinesiotherapy, and occupational therapy (KOP). The programme was introduced into the practice of the hospital, and its outcomes were monitored with a pilot population divided into 2 subprogrammes. CV risk factor prevalence study (n= 5481) as the most common CV risk factors identified hypertension (56.6 %) and smoking (55.7 %), high-risk patients proportion was 1364 (27 %). HSE (n=40) enrolled patients improved their body weight. KOP results show that patients with schizophrenia preferred physical activity less than others; 53 % of patients have no physical activity during hospitalization, and spontaneous physical activity depends on BMI in our sample. We observed improvement in cognitive functioning, perception of physical functions, or perceived limitations was comparable to the general population. Results show the usability of the program design; initial screening with two intervention branches can increase motivation for physical activity and adoption of health-promoting behaviors and support a recovery process in SMI patients. SOMA project is unique in the Czech environment, however, larger sample with longer observation period is needed.
Keywords: kardiovaskulární nemoci; Humans; lidé středního věku; Nutritional care; schizofrenie; rizikové faktory; Female; dospělí; zdravý životní styl; lidé; Schizophrenia; Physiotherapy; Cardiovascular disease; pilotní projekty; Pilot Projects; duševní poruchy; Physical Therapy Modalities; Adult; ženské pohlaví; Cardiovascular Diseases; Male; Middle Aged; Healthy lifestyle education; Mass Screening; Mental Disorders; ergoterapie; techniky fyzikální terapie; plošný screening; mužské pohlaví; Severe mental illness; Healthy Lifestyle; Occupational Therapy; Risk Factors